Alpha Cuts of Fuzzy Basis - M. Muthukumari; A. Nagarajan; M. Murugalingam (International Journal of Mathematics And its Applications, 2015)
We introduce fuzzy basis, strong fuzzy basis and alpha cuts of fuzzy basis and strong fuzzy basis.